Pengaruh Kualitas Layanan, Kualitas Produk dan Nilai Nasabah Terhadap Kepuasan dan Loyalitas Nasabah Bank Mandiri - Rachmad Hidayat (Jurnal Manajemen dan Wirausaha, 2009)
The objectives of this study is to measure customer level of satisfaction and loyalty toward banking service in East Java. This study is categorized as survey research with descriptive analysis method by taking sample from population and using questionnaire as the main data-collecting instrument. The population in this research is all customers of Mandiri Bank in East Java. The respondents are chosen by using probability sampling and systematic random sampling techniques. The research sample is chosen randomly for the first data whereas the following is using certain interval. The results of analysis using Structural Equation Modeling (SEM) model are: (1) Service quality has positive and significant influence on customer satisfaction. (2) Product quality has positive and significant influence on customer satisfaction. (3) Value for customer has positive and significant influence on customer satisfaction. (4) Customer satisfaction has positive, significant influence to customer loyalty. (5) Service quality has negative, significant influence on customer loyalty. (6) Product quality has negative, significant influence on customer loyalty. (7) Value for customer has positive, significant influence on customer loyalty. (8) Theoretical finding leading to the theory developed is service quality has negative, significant influence on customer loyalty. But significant influence on customer satisfaction. And product quality has negative, significant influence on customer loyalty. But positive, significant influence on customer loyalty mediated by customer satisfaction.